(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Corchorus olitorius is a vegetable plant/shrub and the leaves are very nutritious and rich in vitamins, minerals and dietary fibers. The study was carried out to identify the effects two extracts of this plant on the reproductive indices of male Wistar rats Forty-five adult male rats of about 12 weeks old, each weighing about 120g were used for this study, kept in a cage and fed with commercial rat pellets and water was given at ad-libitum. They were randomly divided into groups A, B and C of 15 rats per group. 250mg/kg of the leaf extract was administered orogastrically using once daily for 21 days. Group A and B were treated with methanol and aqueous leaves of Corchorus extract respectively and Group C was given distilled water and served as the control. The weekly sacrifice of five rats per group was done following treatments. In this study, it was observed at the first-week post -treatment that there was significant (p≤0.05) decrease in the PCV and haemoglobin values of group A rats compared to the control group but the values later increased at the second week and third-week post-treatments. There was also a significant decrease in spermatozoa motility in the treated groups A and B compared to the control group C at the first, second- and third-week post treatments. Also, with the results of the serum testosterone level of group A and B compared to group C. The value was higher in group A followed by group B whereas, at the second week and third week, there was no significant difference in the values of the serum testosterone levels compared to the control groups. It is therefore concluded that the methanol and aqueous extract of Corchorus olitorius leaves significantly decreased sperm motility in male albino rats hence could decrease male fertility.